MEMBACA : MOTIVASI & KAEDAH - Zaini Ujang, Prof. Dato' Ir. Dr., 1965-, author; Zinitulniza Abdul Kadir, 1971-, editor; Zalila Isa, editor (Kuala Lumpur : Institut Terjemahan & Buku Malaysia, 2019)
The book reveals 1,001 secrets and tips on reading, as well as sharing a variety of reading techniques, including skimming and scanning that will allow you to read up to 20,000 words per minute. It is a third edition book that has been rewritten, updated and added with new chapters and introductory words, with the aim of helping in overcome various reading problems.